Weakly periodic ground states for the λ-model - Mukhamedov, Farrukh M.; Rahmatullaev, Muzaffar M.; Rasulova, M. A.; Мухамедов, Фаррух Максутович; Рахматуллаев, Музаффар Мухаммаджанович; Расулова, Мухайе Акбаржон; Мухамедов, Фаррух Максутович; Рахматуллаев, Музаффар Мухаммаджанович; Расулова, Мухайе Акбаржон (Institute of Mathematics, NAS of Ukraine, 2020)
For the $λ$-model on a Cayley tree of order $k≥2,$ we describe a set of periodic and weakly periodic ground states that correspond to normal divisors of index 2 of the group representation of the Cayley tree.